Short-Term Outcome of Video Assisted Thoracoscopic Decortication in Empyema Thoracis - Banik, Rajib; Haque, AKM Akramul; Hossain, Md Mobarak; Choudhary, Apurbo Kumar; Rahman Chisty, Mohammad Mahshukur; Rayhan, Mohammad Zannatul; Dhruba, Avishek Sarker (Journal of Current and Advance Medical Research, 2021)
Background: Video-assisted thoracoscopic surgical decortication (VATS Decortication) is one of the technique for treating empyema thoracis. Objective: The purpose of the present study was to assess radiologic and functional short-term outcomes of VATS decortication in comparison with open decortication among empyema thoracis patients. Methodology: This comparative type of observational study was done at Department of Thoracic Surgery at National Institute of Diseases of Chest and Hospital (NIDCH), Dhaka, Bangladesh from July 2018 to June 2019 for a period of one year. Patients with empyema thoracis in stage II or III were included. Short-term outcomes were measured according to collection of chest drain tube in post-operative observational days (PODs), post-operative lung expansion, time taken for chest drain tube removal, postoperative hospital stay and post-operative pain (numeric rating scale) observations up to discharge from hospital. Result: A total number of 70 patients were recruited. The mean age was 36.20 ± 12.50 years. In post-operative phase apical chest drain tube collection followed by VATS procedure was found significantly lower than that of open decortication (2nd POD: p= 0.04; 3rd POD: p =0.039). Both the apical (p=0.001) and basal (p=0.039) chest drain tubes were removed earlier in patients with VATS decortication. Again, patients with VATS decortication had to stay less days in post-operative time (p=0.01). The mean post-operative pain scores was significantly higher among the patients underwent open decortication (p<0.001). Conclusion: VATS decortication has shown better outcome in terms of collection of chest drain tube in post- operative days, time taken for chest drain tube removal, post-operative hospital stay and post-operative pain in managing patients with empyema thoracis. Journal of Current and Advance Medical Research, July 2021;8(2):100-105